An asymmetric composite solid electrolyte membrane and a preparation method and application thereof

CN117712475BActive Publication Date: 2026-10-16GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311820447.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2026-10-16
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

但一方面,该专利需要长时间静置渗透作用方可达到非对称电解质膜效果;另一方面,该专利的固态电解质膜虽然具有一定的强度,在一定程度减缓了锂枝晶的刺破电解质膜的风险,但具体实例也仅是常压下NCM锂二次电池的扣电循环数据,对高电压锂金属二次电池的适配性不可知

Benefits of technology

[0037] The asymmetric composite solid electrolyte membrane of the present invention has the characteristics of high mechanical strength, ultrathinness, high ionic conductivity, high voltage resistance, good lithium stability, good interface compatibility, wide voltage window, low interface resistance, and outstanding room temperature cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117712475B_ABST
    Figure CN117712475B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solid electrolyte, and particularly relates to an asymmetric composite solid electrolyte film and a preparation method and application thereof, wherein a composite electrolyte colloid A layer and a composite electrolyte colloid B layer based on MOF materials are respectively formed on both sides of a high-porosity porous support material, the lithium stability is further enhanced by introducing the MOF material in the application, in addition, the high-porosity support material is introduced into the composite solid electrolyte, the mechanical strength of the film is enhanced while the flexibility of the electrolyte film is ensured, and the risk of short circuit of the battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid electrolyte technology, specifically relating to an asymmetric composite solid electrolyte membrane, its preparation method, and its application. Background Technology

[0002] Solid electrolytes are the core components of solid-state lithium batteries, and their performance directly affects key indicators such as power density, cycle stability, safety, high and low temperature performance, and lifespan of solid-state lithium batteries.

[0003] Currently, solid-state electrolytes can generally be classified into three types: organic polymer solid-state electrolytes, inorganic solid-state electrolytes, and organic-inorganic composite solid-state electrolytes. Organic polymer solid-state electrolytes are characterized by simple preparation methods, good ductility, high flexibility, and excellent film-forming properties, as well as good electrode-electrolyte interface contact. However, they suffer from drawbacks such as poor mechanical properties and low ionic conductivity at room temperature. In particular, their mechanical strength and lithium stability still cannot meet the requirements for stable long-cycle operation of solid-state batteries. Inorganic solid-state electrolytes have higher room-temperature ionic conductivity, but suffer from poor flexibility, poor interfacial compatibility, complex preparation processes, and high costs.

[0004] Composite solid electrolytes are typically prepared by combining inorganic solid electrolytes and organic polymers. They possess high lithium-ion conductivity, high electrochemical and thermodynamic stability, good interfacial compatibility, and the ability to suppress lithium dendrite growth, making them one of the current hot topics in solid electrolyte research.

[0005] Chinese patent CN113285118A discloses a composite solid electrolyte based on a MOF three-dimensional framework and its preparation method. The preparation includes the following steps: casting a lithium salt-polymer solution into a nanofiber material to obtain a composite solid electrolyte with a three-dimensional framework structure; the lithium salt-polymer solution is prepared by mixing lithium salt and polymer in an organic solvent; the nanofiber material is prepared by dissolving and mixing MOF powder and polymer separately, followed by electrospinning. The MOF-based three-dimensional framework support of the composite solid electrolyte not only provides a continuous transport channel for lithium ions, effectively increasing the lithium ion transport number, but also significantly enhances the mechanical properties of the composite solid electrolyte through the combination of its three-dimensional framework and highly interconnected crystal structure, thereby physically inhibiting the growth of lithium dendrites and enabling better application in lithium metal anode secondary batteries. This patent does not mention the electrochemical window, and the specific examples are experimental data obtained at a conventional voltage of 4.2V and 60℃; therefore, its suitability for high-voltage lithium metal secondary batteries is unknown.

[0006] Chinese patent CN115458807A discloses a multilayer composite electrolyte membrane based on a metal-organic framework (MOF) material and its preparation method. The composite electrolyte membrane is an ultrathin asymmetric solid electrolyte composed of a rigid MOF layer with ion-regulating capabilities and an interface-friendly polymer layer. The rigid MOF layer improves the membrane's thermal stability, regulates the uniform deposition of lithium, and has a high elastic modulus that can suppress lithium dendrite growth. The ionic conductivity solution or polymer layer enables good electrode-electrolyte interface contact. Lithium metal symmetric batteries based on this electrolyte exhibit excellent ion uniform deposition stability. Batteries using the composite electrolyte membrane containing the ionic conductivity MOF layer still show excellent electrochemical performance and high safety over a wide temperature range (-20 to 170°C). The patent explicitly states that electrolyte generation requires in-situ polymerization under ultraviolet irradiation or heating. However, this method can lead to uneven polymerization, which may accelerate lithium dendrite growth. Furthermore, the preparation process is complex and cumbersome, hindering industrial production and practical application.

[0007] Chinese Patent Publication No. CN115966755A discloses an organic-inorganic composite solid electrolyte membrane, its preparation method, and its application. The solid electrolyte membrane comprises a porous membrane and an organic-inorganic composite electrolyte layer located on a first surface of the porous membrane. The porous membrane contains a polymer electrolyte. The organic-inorganic composite electrolyte includes a lithium salt, an ether polymer, and an inorganic solid electrolyte. The polymer electrolyte includes a lithium salt and an ether polymer. The ether polymer is formed by ring-opening polymerization of a cyclic ether compound. The thickness of the solid electrolyte membrane is comparable to the thickness of the porous membrane used as a substrate. Furthermore, due to the porous membrane acting as a support, the asymmetric membrane can improve the coin cell cycle performance of NCM lithium secondary batteries under ambient pressure to a certain extent after assembling a coin cell using the above-mentioned solid electrolyte membrane. However, on the one hand, this patent requires a long period of static osmosis to achieve the effect of an asymmetric electrolyte membrane; on the other hand, although the solid electrolyte membrane of this patent has a certain strength, which reduces the risk of lithium dendrites piercing the electrolyte membrane to a certain extent, the specific examples are only the coin cycle data of NCM lithium secondary batteries under normal pressure, and the adaptability to high-voltage lithium metal secondary batteries is unknown. Summary of the Invention

[0008] This invention addresses the shortcomings of existing technologies by proposing an asymmetric composite solid electrolyte membrane, its preparation method, and its application.

[0009] Specifically, this is achieved through the following technical solutions:

[0010] An asymmetric composite solid electrolyte membrane is formed by forming a composite electrolyte colloid A layer and a composite electrolyte colloid B layer based on MOF material on both sides of a porous support material with high porosity.

[0011] The preparation method of the MOF-based composite electrolyte colloid A is as follows: First, the organic polymer and lithium salt are dissolved in an organic solvent and heated to disperse evenly to obtain organic polymer electrolyte colloid C. At the same time, the MOF material and inorganic oxide are dissolved in an organic solvent and dispersed evenly to obtain suspension D. Then, after the organic polymer electrolyte colloid C is cooled to room temperature, the suspension D is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain MOF-based composite electrolyte colloid A.

[0012] The method for preparing the composite electrolyte colloid B is as follows: first, the organic polymer and lithium salt are dissolved in an organic solvent and heated to disperse evenly to obtain organic polymer electrolyte colloid C; at the same time, the inorganic oxide is dissolved in an organic solvent and dispersed evenly to obtain suspension E; then, after the organic polymer electrolyte colloid C cools to room temperature, the suspension E is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain composite electrolyte colloid B.

[0013] The organic polymer is one or more of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polyvinylidene fluoride (PVDF).

[0014] The inorganic oxide is any one or a mixture of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), lithium aluminum germanium phosphate (LAGP), and lithium aluminum titanium phosphate (LATP).

[0015] The lithium salt is any one or a mixture of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonate)imide (LiTFSI).

[0016] The organic solvent is one or more of anhydrous acetonitrile, N,N-dimethylformamide (DMF), N-methylpyrrolidone, and acetone.

[0017] The MOF material is one or two of ZIF-67, ZIF-8, and Zn-Co bimetallic MOF materials, with Zn-Co bimetallic MOF material being preferred.

[0018] The preparation method of the Zn-Co bimetallic MOF material is as follows: Cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and 2-methylimidazole are weighed according to a molar ratio of 1-10:1-10:4-200. Cobalt nitrate hexahydrate, zinc nitrate hexahydrate, and 2-methylimidazole are dissolved in sufficient solvent and labeled as solutions A, B, and C, respectively. The solutions are stirred evenly with a magnetic stirrer at 300-800 r / min. Solution A is slowly added dropwise to solution C, and the mixed solution is labeled as solution D. The solution is ultrasonically stirred evenly. Solution B is slowly added dropwise to solution D, and the solution is ultrasonically stirred for 5 hours at a stirring speed of 300-800 r / min. The above products are washed with solvent and centrifuged three times. The centrifuged products are first dried in a forced-air dryer at 80℃, and then transferred to vacuum drying at 80℃ for 24 hours to obtain Zn-Co MOF material.

[0019] The solvent is any one of methanol, ethanol, and propanol.

[0020] The centrifugation speed was 6000 r / min, and the time was 5 minutes each time.

[0021] The content of the organic polymer is 30% to 60% of the total weight of the solid solute in the asymmetric composite solid electrolyte membrane.

[0022] The lithium salt content is 30% to 65% of the total weight of solid solute in the asymmetric composite solid electrolyte membrane.

[0023] The content of the inorganic oxide is 1% to 15% of the total weight of the solid solute in the asymmetric composite solid electrolyte membrane.

[0024] The content of the MOF material is 0.5% to 15% of the total weight of the organic polymer.

[0025] A method for preparing an asymmetric composite solid electrolyte membrane includes the following steps:

[0026] 1) Preparation of organic polymer electrolyte colloid C: Dissolve organic polymer and lithium salt in organic solvent and heat to disperse evenly to obtain the final product;

[0027] 2) Preparation of suspension D: Dissolve the MOF material and inorganic oxide in an organic solvent and disperse them evenly to obtain the suspension.

[0028] 3) Preparation of suspension E: The inorganic oxide is dissolved in an organic solvent and dispersed evenly to obtain the suspension.

[0029] 4) Preparation of composite electrolyte colloid A: After the organic polymer electrolyte colloid C cools to room temperature, the suspension D is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain the final product;

[0030] 5) Preparation of composite electrolyte colloid B: After the organic polymer electrolyte colloid C cools to room temperature, the suspension E is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain the final product;

[0031] 6) Preparation of asymmetric composite solid electrolyte membrane: Under the condition that the ambient water content is ≤3%, composite electrolyte colloid A and composite electrolyte colloid B are coated on both sides of a porous support material with high porosity, respectively. After vacuum degassing, drying at 50-70℃ and vacuum drying for 24h, an asymmetric composite solid electrolyte membrane with a total thickness ≤20μm is obtained.

[0032] The thickness of the porous support material is ≤10μm.

[0033] The high-porosity porous support material is any one of polyethylene (PE) base film, non-woven fabric diaphragm, or electrospun diaphragm.

[0034] The porosity of the high-porosity porous support material is 30% to 70%.

[0035] Application of an asymmetric composite solid electrolyte membrane in the preparation of electrolytes for high-voltage lithium metal solid batteries.

[0036] Beneficial effects:

[0037] The asymmetric composite solid electrolyte membrane of the present invention has the characteristics of high mechanical strength, ultrathinness, high ionic conductivity, high voltage resistance, good lithium stability, good interface compatibility, wide voltage window, low interface resistance, and outstanding room temperature cycling performance.

[0038] The preparation process of this invention is simple, easy to operate, and low in cost, making it suitable for large-scale commercial production and application.

[0039] In this invention, an asymmetric composite solid electrolyte membrane based on a lithiophilic MOF material is prepared. In practical applications, the composite electrolyte colloid A layer based on the MOF material is in contact with lithium metal, while the composite electrolyte colloid B layer is in contact with the high-voltage positive electrode. This can induce uniform deposition of lithium dendrites, inhibit lithium dendrite growth, and further enhance lithium stability. In addition, the composite solid electrolyte is supported by a porous support material with high porosity, which enhances the mechanical strength of the membrane while ensuring the flexibility of the electrolyte membrane, reduces the risk of battery short circuit, and has the benefit of significantly improving the cycle performance of high-voltage lithium metal batteries.

[0040] The asymmetric composite solid electrolyte membrane of the present invention can be applied to high-voltage lithium metal solid batteries and significantly improves their cycling performance at room temperature. Attached Figure Description

[0041] Figure 1 Optical photograph of the composite solid electrolyte membrane of Example 1;

[0042] Figure 2 LSV diagram of the composite solid electrolyte membrane in Example 1;

[0043] Figure 3 Cycle performance diagram of the battery assembled using the composite solid electrolyte membrane of Example 1;

[0044] Figure 4 Electrochemical stability test results of the battery assembled using the composite solid electrolyte membrane of Example 1;

[0045] Figure 5 Cycle performance diagram of the battery assembled using the composite solid electrolyte membrane of Example 2;

[0046] Figure 6 Cycle performance diagram of the battery assembled using the composite solid electrolyte membrane of Example 3. Detailed Implementation

[0047] The specific embodiments of the present invention will be described in further detail below. However, the present invention is not limited to these embodiments. Any improvements or substitutions based on the basic spirit of these embodiments shall still fall within the scope of protection claimed by the claims of the present invention.

[0048] The MOF materials used in Examples 1-3 are prepared using the following methods:

[0049] (1) Preparation of ZIF-8

[0050] Zinc nitrate hexahydrate and 2-methylimidazole were weighed at a molar ratio of 1:5 and dissolved separately in sufficient methanol. The mixture was mechanically stirred until completely dissolved. The resulting zinc nitrate hexahydrate solution was slowly added dropwise to the 2-methylimidazole solution and ultrasonically stirred for 3 hours at a stirring speed of 450 r / min. The product was washed with methanol and then centrifuged at 6000 r / min for 5 minutes each time, for a total of three centrifugations. The centrifuged product was first dried in a forced-air dryer at 80℃ and then transferred to a vacuum dryer at 80℃ for 24 hours to obtain ZIF-8 white powder.

[0051] (2) Preparation of ZIF-67

[0052] Cobalt nitrate hexahydrate and 2-methylimidazole were weighed at a molar ratio of 1:6 and dissolved separately in 200 mL of methanol. The solutions were mechanically stirred until completely dissolved. The resulting zinc nitrate hexahydrate solution was slowly added dropwise to the 2-methylimidazole solution and ultrasonically stirred for 3 hours at a stirring speed of 450 r / min. The product was washed with methanol and then centrifuged three times at a speed of 6000 r / min for 5 minutes each time. The centrifuged product was first dried in a forced-air dryer at 80 °C and then transferred to a vacuum dryer at 80 °C for 24 hours to obtain purple ZIF-67 powder.

[0053] (3) Preparation of Zn-Co bimetallic MOF materials

[0054] Zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and 2-methylimidazole were weighed at a molar ratio of 1:1:12 and dissolved separately in sufficient methanol, denoted as solutions A, B, and C, respectively. The solutions were mechanically stirred until completely dissolved. Solution A was slowly added dropwise to solution C, and the resulting mixture was denoted as solvent D. The mixture was ultrasonically stirred for 2 hours at a stirring speed of 400 r / min. Solvent B was then slowly added dropwise to solvent D, and the mixture was ultrasonically stirred for 5 hours at a stirring speed of 600 r / min. The product was washed with methanol and then centrifuged three times at 6000 r / min for 5 minutes each time. The centrifuged product was first dried in a forced-air dryer at 80 °C, and then transferred to a vacuum dryer at 80 °C for 24 hours to obtain Zn-Co MOF material.

[0055] Example 1:

[0056] Two portions of LLZTO powder, PVDF-HFP, and LiTFSI were weighed at a mass ratio of 1:10:11. Zn-Co bimetallic MOF material and PVDF-HFP were weighed at a mass ratio of 1:20. PVDF-HFP and LiTFSI were dispersed in DMF and labeled as #1 and #2, respectively. These were placed on magnetic stirrers and heated and stirred at 450 rpm and 60°C until homogeneous. After stirring, the heating was turned off, stirring continued, and the mixture was cooled to room temperature. LLZTO powder was dispersed in the DMF solution and placed on a magnetic stirrer. Stirring was carried out at 500 rpm and room temperature until homogeneous. This mixture was then slowly added dropwise to the aforementioned polymer electrolyte colloid #1 at 600 rpm until fully homogeneous, yielding composite electrolyte slurry A. Zn-Co… Bimetallic MOF material and LLZTO powder were dispersed in another DMF solution and placed on a magnetic stirrer at 500 r / min at room temperature. After stirring evenly, the mixture was slowly added dropwise to the above-mentioned No. 2 polymer electrolyte colloid at 600 r / min and stirred evenly to obtain composite electrolyte slurry B. In a drying room with a water content ≤3%, composite electrolyte slurry A was coated on one side of a 5 μm polyethylene base membrane with a porosity of 33% and dried in a forced-air drying oven at 55°C to obtain a thickness of 8 μm. After drying, composite electrolyte slurry B was coated on the other side of the electrolyte membrane and dried in a forced-air drying oven at 55°C to obtain a thickness of 14 μm. Then, it was transferred to a vacuum drying oven at 60°C and vacuum dried for 24 h to obtain a composite solid electrolyte membrane.

[0057] The optical photograph of the composite solid electrolyte membrane is as follows. Figure 1 It exhibits flexibility and has an electrochemical window > 4.7V, as follows: Figure 2As shown. Solid-state lithium-ion batteries were fabricated using this composite solid-state electrolyte membrane in conjunction with a high-voltage lithium cobalt oxide positive electrode and a lithium metal negative electrode using existing pouch cell technology. A small amount of commercial electrolyte was added at a concentration of 1.5 g / Ah for plasticizing treatment. The assembled LCO / Li pouch cell exhibited a capacity retention of approximately 97.6% after 70 cycles at 0.2C within the range of 3–4.45 V, as shown below. Figure 3 As shown.

[0058] Example 2

[0059] Weigh two portions of LLZTO powder, PVDF-HFP, and LiTFSI at a mass ratio of 1:10:10, and weigh ZIF-67 material and PVDF-HFP at a mass ratio of 1:30. Disperse PVDF-HFP and LiTFSI in DMF, labeling them 1# and 2# respectively. Place them on a magnetic stirrer and heat and stir at 500 rpm and 65°C until homogeneous. After stirring, turn off the heat and continue stirring until cooled to room temperature. Disperse LLZTO powder in DMF solution and place it on a magnetic stirrer. Stir at 500 rpm and room temperature until homogeneous. Slowly add it dropwise to the above-mentioned polymer electrolyte colloid 1# at 650 rpm until fully homogeneous to obtain composite electrolyte slurry A. Add ZIF- Material 67 and LLZTO powder were dispersed in another DMF solution and placed on a magnetic stirrer. The mixture was stirred at 500 r / min at room temperature until homogeneous. Then, it was slowly added dropwise to the above-mentioned polymer electrolyte colloid #2 at 600 r / min until fully homogeneous, resulting in composite electrolyte slurry B. In a drying room with a water content ≤3%, composite electrolyte slurry A was coated on one side of a non-woven fabric membrane with a porosity of 55%. The acetonitrile solvent was dried in a forced-air drying oven at 60°C, resulting in a thickness of 10 μm. After drying, composite electrolyte slurry B was coated on the other side of the electrolyte membrane and dried in a forced-air drying oven at 55°C. Then, it was transferred to a vacuum drying oven at 60°C and vacuum dried for 24 h to obtain a composite solid electrolyte membrane with a total thickness of 17 μm.

[0060] Using this composite solid electrolyte membrane in conjunction with a high-voltage lithium cobalt oxide cathode and a lithium metal anode, the electrochemical stability of a Li / CPE / Li symmetric battery was tested at room temperature and a current density of 0.2 mA / cm². Figure 4 As shown, the Li / CPE / Li symmetric battery can cycle stably for over 500 hours with similar polarization voltages, indicating good lithium stability. Solid-state lithium-ion batteries were fabricated using existing pouch cell technology, with a small amount of commercial electrolyte added at 1.5 g / Ah for plasticization. The assembled LCO / Li pouch cell exhibited a capacity retention of approximately 96.0% after 60 cycles at 0.2C within the 3–4.45V range, as shown below. Figure 5 As shown.

[0061] Example 3

[0062] Weigh two portions of LLZTO powder, PVDF-HFP, and LiTFSI at a mass ratio of 1:10:10, and weigh ZIF-8 material and PVDF-HFP at a mass ratio of 1:15. Disperse PVDF-HFP and LiTFSI in DMF, labeling them 1# and 2# respectively. Place them on a magnetic stirrer and heat and stir at 500 rpm and 65°C until homogeneous. After stirring, turn off the heat and continue stirring until cooled to room temperature. Disperse LLZTO powder in DMF solution and place it on a magnetic stirrer. Stir at 550 rpm and room temperature until homogeneous. Slowly add it dropwise to the above-mentioned polymer electrolyte colloid 1# at 650 rpm until fully homogeneous to obtain composite electrolyte slurry A. Add ZIF- 8. The LLZTO powder was dispersed in another DMF solution and placed on a magnetic stirrer. The mixture was stirred at 500 r / min at room temperature until homogeneous. Then, it was slowly added dropwise to the above-mentioned No. 2 polymer electrolyte colloid at 600 r / min until fully homogeneous, resulting in composite electrolyte slurry B. In a drying room with a water content ≤3%, composite electrolyte slurry A was coated on one side of an electrospun membrane with a porosity of 65%. The acetonitrile solvent was dried in a forced-air drying oven at 60°C, resulting in a thickness of 9 μm. After drying, composite electrolyte slurry B was coated on the other side of the electrolyte membrane and the acetonitrile solvent was dried in a forced-air drying oven at 55°C. Then, it was transferred to a vacuum drying oven at 60°C and vacuum dried for 24 h to obtain a composite solid electrolyte membrane with a total thickness of 16 μm.

[0063] Solid-state lithium-ion batteries were fabricated using this composite solid-state electrolyte membrane in conjunction with high-voltage lithium cobalt oxide cathode and lithium metal anode using existing pouch cell technology. A small amount of commercial electrolyte was added at a concentration of 1.5 g / Ah for plasticization. The assembled LCO / Li pouch cell exhibited a capacity retention of approximately 86.7% after 50 cycles at 0.2C within the range of 3–4.45 V, as follows: Figure 6 As shown.

Claims

1. An asymmetric composite solid electrolyte membrane, characterized in that, A composite electrolyte colloid A layer and a composite electrolyte colloid B layer based on MOF material are formed on both sides of a porous support material with high porosity. The preparation method of the MOF-based composite electrolyte colloid A is as follows: First, the organic polymer and lithium salt are dissolved in an organic solvent and heated to disperse evenly to obtain organic polymer electrolyte colloid C. At the same time, the MOF material and inorganic oxide are dissolved in an organic solvent and dispersed evenly to obtain suspension D. Then, after the organic polymer electrolyte colloid C is cooled to room temperature, the suspension D is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain MOF-based composite electrolyte colloid A. The preparation method of the composite electrolyte colloid B is as follows: first, the organic polymer and lithium salt are dissolved in an organic solvent and heated to disperse evenly to obtain organic polymer electrolyte colloid C; at the same time, the inorganic oxide is dissolved in an organic solvent and dispersed evenly to obtain suspension E; then, after the organic polymer electrolyte colloid C is cooled to room temperature, the suspension E is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain composite electrolyte colloid B. The porosity of the high-porosity porous support material is 30% to 70%; The organic polymer, inorganic oxide, lithium salt, and organic solvent in the composite electrolyte colloid A and composite electrolyte colloid B based on MOF material are the same. The organic polymer is one or more mixtures of PVDF-HFP and PVDF. The inorganic oxide is any one or more mixtures of LLZO, LLTO, LLZTO, LAGP, and LATP. The lithium salt is any one or more mixtures of LiFSI and LiTFSI. The organic solvent is one or more of anhydrous acetonitrile, DMF, N-methylpyrrolidone, and acetone. The MOF material is one or two of ZIF-67, ZIF-8, and Zn-Co bimetallic MOF materials. The total thickness of the asymmetric composite solid electrolyte membrane is ≤20μm, and the thickness of the porous support material is ≤10μm. The high-porosity porous support material is any one of polyethylene-based membrane, non-woven membrane, or electrospun membrane.

2. The method for preparing an asymmetric composite solid electrolyte membrane as described in claim 1, characterized in that, Includes the following steps: 1) Preparation of organic polymer electrolyte colloid C: Dissolve organic polymer and lithium salt in organic solvent and heat to disperse evenly to obtain the final product; 2) Preparation of suspension D: Dissolve the MOF material and inorganic oxide in an organic solvent and disperse them evenly to obtain the suspension. 3) Preparation of suspension E: The inorganic oxide is dissolved in an organic solvent and dispersed evenly to obtain the suspension. 4) Preparation of composite electrolyte colloid A: After the organic polymer electrolyte colloid C cools to room temperature, the suspension D is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain the final product; 5) Preparation of composite electrolyte colloid B: After the organic polymer electrolyte colloid C cools to room temperature, the suspension E is slowly added dropwise to the organic polymer electrolyte colloid C and stirred evenly to obtain the final product; 6) Preparation of asymmetric composite solid electrolyte membrane: Under the condition that the ambient water content is ≤3%, composite electrolyte colloid A and composite electrolyte colloid B are coated on both sides of a porous support material with high porosity, respectively. After vacuum degassing, drying at 50-70℃ and vacuum drying for 24h, an asymmetric composite solid electrolyte membrane with a total thickness ≤20μm is obtained.

3. The application of the asymmetric composite solid electrolyte membrane as described in claim 1 in the preparation of high-voltage lithium metal solid battery electrolytes.

Citation Information

Patent Citations

  • Composite solid electrolyte based on MOF three-dimensional skeleton support, and preparation method thereof

    CN113285118A

  • Multi-layer composite electrolyte membrane based on metal-organic framework material and preparation method of multi-layer composite electrolyte membrane

    CN115458807A

  • Organic-inorganic composite solid electrolyte membrane and preparation method and application thereof

    CN115966755A